Quantitative evaluation of effectiveness of Hospital Mesra Ibadah Course: A pre post study - Kow, Ren Yi; Md Hashim, Mohd Jumaidi; Nazhar, Anas; Mor Japar Khan, Ed Simor Khan; Low, Chooi Leng (2019)
Introduction Solat or prayer, as one of the five pillars of Islam, and it is associated with bio psycho social benefits in Muslim patients. Many Muslim patients neglected solat while being hospitalized as they are unaware of the convenience (rukhsoh) available for them. Ibadah Friendly Hospital Courses have been conducted in different states of Malaysia to impart knowledge to the hospital staff who can in turn educate their patients. This study aims to construct a content validated assessment tool and to assess the effectiveness of a state level Hospital Mesra Ibadah course.\ Materials and methods A self administered questionnaire was constructed and content validated by a panel of three experts (two religious teachers and one consultant spine surgeon). All 15 questions achieved item level content validity index (ICVI) of 1.00 after two rounds of validation. The questionnaires were distributed to participants of a state level Hospital Mesra Ibadah course to compare the participants’ pre course test score and post course test score. The participants were from tertiary hospitals (Hospital Tengku Ampuan Afzan, Hospital Sultan Ahmad Shah and Hospital Kuala Lipis), district hospitals (Hospital Jengka, Hospital Jerantut, Hospital Rompin, Hospital Bentong and Hospital Raub) and other health clinics. Results A total of 88 participants (48.9%) were included in this study. There was a significant difference in the pre course test mean score and post course test mean score among the participants. There was also a significant reduction of unsure answer after the course. Discussions This study is the first of its kind in Malaysia that quantitatively assess the initial knowledge and subsequent improvement after the course. A reasonable number of participants completed both the pre and post test assessment, reflecting on the positive attitude the participants had on this topic. The participants are of different occupations as well as different hospitals, thus increases the generalizability of this study results. Although the sample size was adequate to get a significant result, response bias may limit the generalizability of this study results. Response bias due to sampling method involving a self administered questionnaire is possible as those with greater interest in the course may have been more likely to respond to the questionnaire. Since the post course assessment was performed immediately after the completion of the course, it was not known whether the course had any long term effect on the participants. On top of that, the knowledge questions just tested certain important pieces of knowledge and may not adequately represent overall knowledge of the participants. Despite these limitations, this is the first of its kind study in Malaysia that quantitatively assesses the effectiveness of the Hospital Mesra Ibadah Course with a content validated questionnaire. Conclusion This study demonstrates that the Hospital Mesra Ibadah course is effective in imparting as well as consolidating the knowledge among participants, hence it should be routinely organized to benefit more participants.